Selectable single-mode guided waves for multi-type damages localization of plate-like structures using film comb transducers. Issue 1 (2nd January 2023) - Ding, Taotao; Wan, Qiang; Xiang, Yanxun; Qiu, Xunlin; Deng, Mingxi; Xuan, Fu-Zhen
ABSTRACT: The dispersion and multimode natures of guided waves bring forth difficulties in signal analysis, limiting the application of traditional transducers. In this paper, we report the design, fabrication and characterisation of transducers composed of a polyvinylidene fluoride (PVDF) film with comb electrodes that can excite selectable single-mode guided waves for high-precision damage diagnosis and localization. The frequency response of the PVDF comb transducers was analysed with respect to the geometric parameters of the comb electrodes, and the sound-field directivity was determined by measuring the in-plane and out-of-plane displacements of the far field around the transducers by means of a double-wave mixed interferometer. In experimental measurements, a surface damage was located using such a PVDF comb transducer to excite single A0 and S2 mode guided waves. In addition, quarter omnidirectional PVDF comb transducers were fabricated and deployed on the corners of a square 7075 aluminium alloy plate  for locating multi-type damages. It is found that the proposed quarter omnidirectional PVDF comb transducers are capable of locating multi-type damages with high accuracy. The PVDF comb transducers has the capability of the guided waves mode selection and flexibility, which is expected to achieve high-precision, long-time and online multi-type damages detection and monitoring.